Tacrolimus Elimination in Four Patients With a CYP3A5*3/*3 CYP3A4*22/*22 Genotype Combination. Issue 7 (27th June 2018) - Scheibner, Aileen; Remmel, Rory; Schladt, David; Oetting, William S.; Guan, Weihua; Wu, Baolin; Dorr, Casey; Israni, Ajay; Jacobson, Pamala A.
Abstract : Cytochrome P450 3A5 (CYP3A5) and cytochrome P450 3A4 (CYP3A4) are the predominate enzymes responsible for tacrolimus metabolism. The presence of CYP3A4 and CYP3A5 genetic variants significantly affects tacrolimus clearance and dose requirements. CYP3A5*3 is a loss‐of‐function variant resulting in no CYP3A5 enzyme production. CYP3A4*22 is a variant that reduces production of functional CYP3A4 protein. Caucasians commonly carry these variant alleles but are very rarely homozygous for both CYP3A5*3 and CYP3A4*22 . This report describes four kidney transplant recipients who carry a rare genotype combination ( CYP3A5*3/*3 and CYP3A4*22/*22 ). These patients were identified from a larger cohort of Caucasian kidney transplant recipients (n=1366). To understand the significance of this genotype combination on tacrolimus troughs and doses, we compared these patients to recipients without this combination. Patients homozygous for both variants are at risk for profound reductions in metabolism of CYP3A substrates. A 342% and a 90.6% increase in the median dose‐normalized trough was observed, when the CYP3A5*3/*3 and CYP3A4*22/*22 genotype combination was compared to the CYP3A5*1/*1 and CYP3A4*1/*1 genotype combination and the CYP3A5*3/*3 and CYP3A4*1/*1 genotype combination, respectively. These four individuals only required on average 2.5 mg/day of tacrolimus. Knowledge of these genotypes would be useful in selecting appropriate tacrolimus doses to avoid overexposure.